2019
DOI: 10.3390/en12091629
|View full text |Cite
|
Sign up to set email alerts
|

Target Setting Outlook for New Residential Building Energy Efficiency Promotion in China: A Frontline Perspective Using Delphi

Abstract: Promoting energy efficiency (EE) requirements for new residential buildings has been proven to be an effective way to slow down the rapid increase of energy consumption. Its successful implementation relies significantly on the attitudes and participation of various stakeholders within the industry, yet they are normally taken for granted. This paper explores and reports both the consensus among and the diversity of the attitudes of frontline stakeholders toward future EE requirements in the new residential bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…However, it also has limitations. Li et al (34) identified several limitations of the method, one of which is that a Delphi study is time-consuming to complete because the process includes multiple iterations or rounds. Additionally, the Delphi technique is very sensitive to design characteristics and the clarity of the question formulation.…”
Section: Delphi Methodsmentioning
confidence: 99%
“…However, it also has limitations. Li et al (34) identified several limitations of the method, one of which is that a Delphi study is time-consuming to complete because the process includes multiple iterations or rounds. Additionally, the Delphi technique is very sensitive to design characteristics and the clarity of the question formulation.…”
Section: Delphi Methodsmentioning
confidence: 99%